Diatom-driven recolonization of microbial mat-dominated siliciclastic tidal flat sediments - Pan, Jerónimo (2017)
Modern microbial mats and biofilms play a paramount role in sediment biostabilization. When sporadic storms affect tidal flats of Bahía Blanca Estuary, the underlying siliciclastic sediment is exposed by physical disruption of the mat, and in a few weeks’ lapse, a microbial community re-establishes. With the objective of studying colonization patterns and the ecological succession of microorganisms at the scale of these erosional structures, these were experimentally-made and their biological recolonization followed for 8 wk, with replication in winter and spring. Motile pennate diatoms led the initial colonization following two distinct patterns: a dominance by Cylindrotheca closterium in winter; and by naviculoid and nitzschioid diatoms in spring. During the first 7 d, cell numbers increased 2-17-fold. Cell densities further increased exhibiting sigmoidal community growth, reaching 2.9-8.9 × 106 cells cm-3 maxima around d-30; centric diatoms maintained low densities throughout. In the 56 d after removal of the original mat, filamentous cyanobacteria that dominates mature mats did not establish a significant biomass, leading to the rejection of the hypothesis that cyanobacteria would drive the colonization. The observed dominance of pennate diatoms is attributed to extrinsic factors determined by tidal flooding; and intrinsic ones, e.g. motility, nutrient affinity, and high growth rate.